Pengaruh Konsentrasi Perekat Kitosan Terhadap Sifat Fisik dan Mekanik Papan Partikel Tiga Lapis Berbahan Limbah Batang Jagung Untuk Aplikasi Meja Ramah Lingkungan - Dicky Setyo Purnomo Dicky; Kardiman; Lilik Astari (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The growing demand for eco-friendly composite materials has driven research into the use of agricultural waste as a substitute for wood-based raw materials. Conventional adhesives such as urea-formaldehyde (UF) and phenol-formaldehyde (PF) contain toxic formaldehyde compounds, making the development of natural alternatives essential. This study investigates the effect of chitosan adhesive concentration and layer arrangement on the physical and mechanical properties of particleboard made from corn stalk (Zea mays L.) waste, intended for environmentally friendly table applications. Corn stalk particles were processed using a hammer mill and bonded with chitosan adhesive at concentrations of 20%, 25%, and 30%. The boards were hot-pressed at 180°C under 30 MPa for 10 minutes and evaluated according to the Japanese Industrial Standard JIS A 5908:2003, covering density, moisture content (MC), water absorption, thickness swelling, Modulus of Elasticity (MOE), and Modulus of Rupture (MOR). Results showed that density values across all treatments (0.46–0.50 g/cm³) met the JIS standard, classifying the boards as medium density particleboard. Moisture content complied with the standard only at 20% and 25% chitosan concentrations. The 30% chitosan concentration yielded the highest mechanical performance (MOE = 654.98 N/mm²; MOR = 2.81 N/mm²), though all treatments fell below the minimum MOE threshold required by the standard. Water absorption and thickness swelling remained high across all treatments, indicating limited dimensional stability.